Sinergitas Industri Lokal Penyelenggara Wisata MICE dan Event di Destinasi Pariwisata Super Prioritas (DPSP) Mandalika - Satiadji, Amirosa Ria (Politeknik Pariwisata NHI Bandung, 2023)
Event is one of tourist attraction that can invite more people to come in a destination. As Nusa Tenggara Barat (NTB) has Mandalika as one of Super Priority Tourism Development di Indonesia created two big event named World Superbike (WSBK) and Moto GP all tourism stakeholder should collaborate to ensure that the development will positively impactful for the society welfare. The governor of NTB create event as a tool for destination marketing. The aim of this research is to know how to develop an impactful event as attraction and bring positive impact to the society. Using qualitative method by interviewing the key informant and continuing with snowball than data triangulation this research has been given a recommendation to planning a creative event. Sewing Model in Event Creative Planning is a model to make an event became larger, gaining resources and giving more over impact to the stakeholder such as government, media, industry, society and education institution (Penta helix). To build the synergy things that all partners must have are: 1. Creative; 2. Have a good network; 3. Trustable; 4. Having permits for creating event; 5. Have a good communication skill; 6. Willingness for beneficial collaboration; 7. A win-win agreement. The collaborations will be successful if all the stakeholders get a positive impact. The organizer has to be ensured that the event created is a sustainable event that bring welfare to all stakeholder, such as support local industry, creative economy by bringing buyer to the event, involving the culinary industry, arts, and encouraging for the development of a sustainable tourism destination for the next generation of the society. Keywords: Creative Event, Stakeholder, Tourism, Marketing, Sustainability.